Wetland vegetation changes in response to climate change and human activities on the Tibetan Plateau during 2000–2015 - Chen, Yuhan; Sun, Lu; Xu, Jiangqi; Liang, Boyi; Wang, Jia; Xiong, Nina (Frontiers in Ecology and Evolution, 2023)
The Tibetan Plateau (TP), known as the third pole, is the highest plateau in the world. It has numerous wetlands, which are important ecological security barriers and plays an important role in mitigating global climate change. This paper employed breaks for additive seasonal and trend (BFAST) algorithm for the mutation detection of the monthly normalized difference vegetation index (NDVI) in wetlands. In addition, correlation analysis and residual analysis were used to study the response of climate change and human activities to NDVI of alpine wetland vegetation in the TP during 2000–2015. The results indicate that the NDVI showed a weak upward trend of 0.009/10a (P < 0.05) with the climate presenting a trend of dry heat development. The NDVI of the growing season was greatly affected by temperature factors with the highest correlation coefficient of 0.686 (P < 0.01). The temperature in the month before and solar radiation in the 3 months before also presented a time lag effect on NDVI, and their correlation coefficients were 0.574 (P < 0.05) and 0.636 (P < 0.05), respectively. Additionally, human activities may have a positive impact on the wetland after 2008. This study explored, for the first time, the NDVI variations of the dynamic wetland and their correlations with temperature, precipitation and solar radiation.